'One-pot' sequential deprotection/functionalisation of linear-dendritic hybrid polymers using a xanthate mediated thiol/Michael addition. Issue 4 (16th October 2014) - Auty, Sam E. R.; Andrén, Oliver C. J.; Y. Hern, Faye; Malkoch, Michael; Rannard, Steven P.
Abstract : Xanthate functional dendritic ATRP macroinitiators, synthesised via a new orthogonal strategy, have been used to form a library of linear-dendritic hybrids via one-pot, post polymerisation, deprotection/acrylate Michael addition. Abstract : Thiol–Michael addition chemistry is a powerful tool for the preparation of functional materials. In this first report of xanthate-functional linear-dendritic polymer hybrids, the preparation of four generations of xanthate-functionalised dendron atom transfer radical polymerisation macroinitiators is described using an orthogonal chemical strategy. The controlled polymerisation of tertiary butyl methacrylate is demonstrated to high conversion and without interference from the xanthate surface groups. Modification of the peripheral xanthate groups of dendrons at the hybrid polymer chain-end has been studied using a one-pot deprotection/functionalisation strategy and a range of commercially available and bespoke acrylate monomers to form complex polymer architectures from feedstock polymers, differing in the number of modified end groups and the surface chemistry of the dendron chain end.